PENGARUH KAJIAN EKONOMI KREATIF BERBASIS BUDAYA LOKAL SEBAGAI UPAYA PENINGKATAN PENDAPATAN MASYARAKAT DESA BENOA - Anak Agung Istri Setiari JMH; I Made Sujana; Ni Luh Wulani Parwati; Putu Ratna Windusara Putri (Nusantara Hasana Journal, 2023)
This study aims to analyze the influence of local culture-based creative economy on increasing community income in Benoa Village, Badung Regency, Bali. Benoa Village possesses various local cultural potentials that can be developed as creative economic resources, including performing arts, traditional crafts, local culinary products, and cultural activities related to tourism. This research employed a descriptive quantitative approach using a survey method. Data were collected through observation, interviews, documentation, and questionnaires distributed to creative economy actors in Benoa Village. Data analysis was conducted using simple regression analysis to determine the relationship between local culture-based creative economy and community income improvement. The findings indicate that the local culture-based creative economy has a positive and significant effect on community income. The development of community creativity supported by cultural preservation can create employment opportunities, increase product value, expand market access, and strengthen local identity. Therefore, collaboration among village governments, communities, and business actors is necessary to strengthen a sustainable creative economy ecosystem.